Achaemenid History, I: Sources, Structures and Synthesis. Proceedings of the Groningen 1983 Achaemenid History Workshop (1987)
Third Achaemenid History Workshop, “The last century of the Achaemenid Empire: Decadence?”, Groningen, May 13-14, 1983.